PENINGKATAN PENGUASAAN MATERI GERAK MELINGKAR BERATURAN MELALUI IMPLEMENTASI PERMAINAN LUDO DALAM SETTING TEAMS GAME TOURNAMENT - Sahetapy, Mariana S.; Tamaela, Elsina (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2025)
Abstract; Improving material mastery is a crucial aspect of the learning process and serves as the ultimate goal to be achieved. One method that can be used to enhance conceptual understanding is the cooperative learning model of Teams Games Tournament (TGT) by implementing the ludo game. This study aims to analyze the improvement in mastery of Uniform Circular Motion through the application of the ludo game in the TGT model at SMA Negeri 8 Ambon, involving 20 eleventh-grade students as research subjects. This study employs a one-group pretest-posttest design, with data collected through test and non-test techniques. The obtained data were then analyzed using a quantitative descriptive method. The research findings indicate that, in the initial stage, all students (100%) failed, with an average score of 12.29. However, during the learning process, there was a significant improvement in material mastery, as shown by an average score of 84.52. In the final stage, material mastery remained in the good category, with an average score of 82.50. Furthermore, the N-Gain test calculation showed a very high increase, with an average score of 0.80. Therefore, this study proves that implementing the ludo game in the TGT learning model is effective in enhancing students' mastery of Uniform Circular Motion.